2009
DOI: 10.1103/physrevb.80.081413
|View full text |Cite
|
Sign up to set email alerts
|

Thermopower and Nernst effect in graphene in a magnetic field

Abstract: We report measurements of the thermopower S and Nernst signal Syx in graphene in a magnetic field H. Both quantities show strong quantum oscillations vs. the gate voltage Vg. Our measurements for Landau Levels of index n = 0 are in quantitative agreement with the edge-current model of Girvin and Jonson (GJ). The inferred off-diagonal thermoelectric conductivity αyx comes close to the quantum of Amps per Kelvin. At the Dirac point (n = 0), however, the width of the peak in αyx is very narrow. We discuss feature… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

58
288
4
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(362 citation statements)
references
References 21 publications
58
288
4
5
Order By: Relevance
“…This is because, except for the n = 0 LL, ௬௫ crosses zero and changes sign whenever the gate voltage V g is located in between adjacent LLs or in the middle of a Landau level (LL). [10][11][12][13] Our measured clearly has only one peak at each n = ±1 LLs, similar to ௫௫ (Fig. S2-3 …”
Section: S22 Thermal Contributionmentioning
confidence: 49%
“…This is because, except for the n = 0 LL, ௬௫ crosses zero and changes sign whenever the gate voltage V g is located in between adjacent LLs or in the middle of a Landau level (LL). [10][11][12][13] Our measured clearly has only one peak at each n = ±1 LLs, similar to ௫௫ (Fig. S2-3 …”
Section: S22 Thermal Contributionmentioning
confidence: 49%
“…It was shown that the sign of Seebeck coefficients changes as the majority carrier density shifts from the electron to that of the hole. The gate-dependent Seebeck coefficient and Nernst signal on graphene in a magnetic field was studied by Ong et al [6]. Quantities closely related to σ are mobility (µ F E ) and resistivity (ρ).…”
Section: Introductionmentioning
confidence: 99%
“…The experimental works carried out by various groups such as Kim et al [4], Geim et al [15], Ong et al [6], Nam arXiv:1703.00224v1 [cond-mat.mtrl-sci] 1 Mar 2017 et al [16] and Wang et al [17] on gate-dependent electron transport properties of MLG and BLG have motivated us to carry out computational studies based on firstprinciples calculations of MLG-doped hexagonal boron nitride (h-BN) and pure BLG under the influence of an electric field, since there is a direct correspondence between gate voltage and chemical potential. It is observed that S is strongly dependent on the amount of doping in the case of MLG.…”
Section: Introductionmentioning
confidence: 99%
“…Phonon-drag thermopower has been extensively studied in bulk semiconductors [20], the conventional 2DEG in semiconductor heterostructures [21][22][23] and graphene systems [24], and it is shown to be generally important at low temperatures. Experimental observations in graphene flakes on substrates hundreds of nanometres in lateral size [25][26][27][28] show no signature of S g , which is attributed to the weak el-ph coupling. However, theoretical studies in freely suspended monolayer [29,30] and bilayer [31] graphene of size ~ 10μm considering the electron-acoustic phonon coupling via deformation potential show S g to be important for temperatures T ≤ 10 K. In graphene nano-ribbons, S g is shown to be of order 1 mV/K and sensitive to the Fermi energy and width of the ribbon [32].…”
Section: Introductionmentioning
confidence: 99%